1989
DOI: 10.1590/s0034-89101989000600003
|View full text |Cite
|
Sign up to set email alerts
|

Tabus alimentares em região do Norte do Brasil

Abstract: RESUMO: Foi realizado um inquérito sobre tabus alimentares em duas localidades do Município de Marabá, PA, Brasil: São Félix e Murumuru, tendo sido estudadas, respectivamente, 90 e 35 famílias. Dos tabus alimentares encontrados, foi grande a restrição feita à ingestão simultânea de leite com várias frutas, especialmente com manga, laranja, cajú e abacaxi; também a ingestão simultânea de ovos com frutas foram referidas como hábitos que devem ser evitados, assim como a mistura de carne de mamíferos com peixes. Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
11

Year Published

1992
1992
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 4 publications
1
8
0
11
Order By: Relevance
“…Such aspect has also been shown in other studies, e.g., Trigo et al (1989), who studied the food taboos of mothers living in Marabá (PA) with children under five years and found that fish food taboos are related to the leather species (very abundant in the region) and these are, in their most, banned in human physiological states such as pregnancy and lactation.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…Such aspect has also been shown in other studies, e.g., Trigo et al (1989), who studied the food taboos of mothers living in Marabá (PA) with children under five years and found that fish food taboos are related to the leather species (very abundant in the region) and these are, in their most, banned in human physiological states such as pregnancy and lactation.…”
Section: Resultssupporting
confidence: 69%
“…From the ecological point of view, preferences or aversions can be explained, among other factors, by resource availability and species location in the food chain (Trigo et al 1989, Begossi et al 2004.…”
Section: Introductionmentioning
confidence: 99%
“…No Brasil, país de amplitude continental, o panorama alimentar é complexo e peculiar 6 . Os fatores geográficos e as culturas dos povos negros, indígenas e brancos, associados à religiosidade popular, conduzem a diversidade de hábitos alimentares locais, caracterizando, assim, cada região do País.…”
Section: N T R O D U ç ã Ounclassified
“…No subitem 1c os estudos manejaram conceitos antropológicos como padrões culturais, tabus, crenças, tradições, conhecimentos e significados, originários de diferentes teorias 38,[45][46][47][48][49][50][51] .…”
Section: Como a Pesquisa Qualitativa Incorporou-se Aos Estudos Da áReunclassified